If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(2x + -6) = 2x + -9 Reorder the terms: 3x + -2(-6 + 2x) = 2x + -9 3x + (-6 * -2 + 2x * -2) = 2x + -9 3x + (12 + -4x) = 2x + -9 Reorder the terms: 12 + 3x + -4x = 2x + -9 Combine like terms: 3x + -4x = -1x 12 + -1x = 2x + -9 Reorder the terms: 12 + -1x = -9 + 2x Solving 12 + -1x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -1x + -2x = -9 + 2x + -2x Combine like terms: -1x + -2x = -3x 12 + -3x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -3x = -9 + 0 12 + -3x = -9 Add '-12' to each side of the equation. 12 + -12 + -3x = -9 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -9 + -12 -3x = -9 + -12 Combine like terms: -9 + -12 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| 4x^2-20x+155=0 | | 6+4x=6+4x | | c=5t-2 | | -24+6y=-6 | | 2+5(6n-1)=-63 | | 6x=57.6 | | 4+x+1=8 | | 3.2x=26.6 | | 1.2=y-0.21 | | -5(m-8)=27-7m | | 2a+7-6a= | | 1-21x=-20-9x | | -8+7n+8n^2=0 | | 3(2n+5)=33 | | 2n-5=25 | | -2(8x+2)=-16x+2 | | 2z+5(3z-6)= | | 17-3(2n-5)=30-6n | | X-3(-2)=5 | | Log[4]6-log[4]-2x=1 | | (2X)-13=X+12 | | 7n+3(4n+8)=5 | | 3t-29=32+4t | | 4x+11y=213 | | X+12=(2*x)-13 | | 4.3x=4.3x | | 4y-32=12x | | (5x-1)+(2x+3)= | | 3y-10-15y=-6y+14 | | 4+8r=-4+7r | | 5.5x+7-1.5x=3.2-3 | | 3w+9=-15 |